New Geographies of the American West - R.Travis William (Island Press, 2007)
Reconciling explosive growth with often majestic landscape defines New Geographies of the American West. Geographer William Travis examines contemporary land use changes and development patterns from the Mississippi to the Pacific, and assesses the ecological and social outcomes of Western development.